Assessing surgical trauma in robot-assisted pelvic fracture fixation: the role of the systemic immune-inflammatory index - Yong-tao, Zhang; Jing, Niu; Xin-zhi, Chen; Hai-liang, Yang; Quan-jie, He; Huan, Liu (Frontiers in Surgery, 2025)
ObjectiveThis study aims to evaluate the association between the systemic immune-inflammation index (SII) and the degree of surgical invasiveness in patients undergoing robot-assisted fixation for anterior pelvic ring fractures.MethodsThis study enrolled patients aged 18–80 years with anterior pelvic ring fractures who underwent INFIX internal fixation, either with or without robotic assistance, between July 2022 and December 2023. Participants were categorized into two groups based on the use of robot-assisted techniques. Exclusion criteria included the presence of multiple fractures requiring additional internal fixation, pre-existing infections, or underlying conditions that could influence inflammatory blood markers. Operative duration, intraoperative blood loss, and incidence of lateral femoral cutaneous nerve (LFCN) injury were documented. The SII was assessed both pre- and postoperatively. Statistical analyses were performed using t-tests. Receiver operating characteristic (ROC) curves were generated to evaluate the predictive performance of SII regarding surgical invasiveness, with optimal cut-off values determined using the Youden index.ResultsA total of 41 patients were included in the study. No significant differences in gender or age were observed between the robot-assisted and non-robot-assisted groups. Compared to the non-robot-assisted group, the robot-assisted group demonstrated significantly shorter operative duration, reduced intraoperative bleeding, and a lower incidence of LFCN palsy (P < 0.05). In addition, the postoperative SII was significantly lower in the robot-assisted group (P < 0.05). ROC curve analysis revealed that postoperative SII exhibited a predictive capability for surgical invasiveness, with an optimal cut-off value of 745.15 (area under the curve = 0.81; sensitivity, 75%; specificity, 83.3%).ConclusionThe findings suggest that the postoperative SII may serve as a valuable biomarker reflecting the degree of surgical invasiveness associated with robot-assisted or conventional INFIX procedures for anterior pelvic ring fractures. A postoperative SII value exceeding 745.15 demonstrates promising predictive utility for elevated surgical trauma, with a specificity of 83.3% and sensitivity of 75%.